2014
DOI: 10.3724/sp.j.1006.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of AcAMP-sn Transgenic Wheat with Enhanced Resistance to Wheat Take-all

Abstract: Antimicrobial peptides, small molecular weight proteins with broad spectrum antimicrobial activity, play important roles in plant defense responses. The open-reading-frame sequence of AcAMP-sn was synthesized and used to construct the gene transformation vector pAHC25::AcAMP-sn, in which AcAMP-sn gene was driven by maize ubiquitin promoter and should be highly expressed in monocot plants. The vector pAHC25::AcAMP-sn DNA was introduced into Yangmai 18 via particle bombardment. AcAMP-sn transgenic wheat plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…SignalP4.0 and NCBI blastp showed that the DmAMP1W protein contained a signal peptide (locating number 1-28 AA residues) and a Knot1 domain (at 30 to 78 AA) harboring eight cysteines (Supplemental Figure S1). The DmAMP1W mature peptide was identical to that of DmAMP1 [35] (Supplementary Figure S2).…”
Section: Heterogonous Expression and Purification Of Dmamp1wmentioning
confidence: 83%
“…SignalP4.0 and NCBI blastp showed that the DmAMP1W protein contained a signal peptide (locating number 1-28 AA residues) and a Knot1 domain (at 30 to 78 AA) harboring eight cysteines (Supplemental Figure S1). The DmAMP1W mature peptide was identical to that of DmAMP1 [35] (Supplementary Figure S2).…”
Section: Heterogonous Expression and Purification Of Dmamp1wmentioning
confidence: 83%